External electromagnetic field-aided freezing of CMC-modified graphene/water nanofluid. (15th January 2016) - Jia, Lisi; Chen, Ying; Lei, Shijun; Mo, Songping; Luo, Xianglong; Shao, Xuefeng
Highlights: Rejection of graphenes by freezing interface causes the aggregation of graphenes. Effect of surfactant on improving graphene aggregation is limited. Effect of electromagnetic field on promoting graphene engulfment is significant. Critical velocity for graphene engulfment is obtained. Abstract: Graphene/water nanofluids with and without surfactant carboxyl methyl cellulose (CMC) were prepared using ultrasonic vibration. Surfactant CMC caused the change in the zeta potential of graphene/water nanofluid from 3.9 mV to −53.1 mV. The CMC-modified graphene/water nanofluid then froze with and without an external electromagnetic field and melted at room temperature. The particle size distributions and adsorption spectra of graphene/water nanofluid after a freeze/melt cycle at different current intensities were measured to evaluate the electromagnetic field effect on graphene rejection and engulfment by the advancing ice–water interface. Results show that (1) without an electromagnetic field, the absorbance of graphene/water nanofluid dramatically reduces, and a new peak of large particle size emerges after a freeze/melt cycle, thereby indicating that graphenes are partially rejected by the ice–water front and aggregate together; and (2) with an electromagnetic field, the adsorption spectra and the particle size distributions of graphene/water nanofluid do not significantly change after a freeze/melt cycle, thereby indicating that the graphenes are captured by the freezing interface and are uniformly distributed in the frozen body of graphene/water nanofluid. The electromagnetic field effect is closely related to the electric current intensity. Good thermal cycling stability can be achieved for graphene/water nanofluid in the current range of 0.07–0.12 A. Mechanisms associated with surfactant adsorption, electromagnetic field, and possible gas evolution are proposed in this study to account for the behavior of graphenes in front of the ice–water interface.